2013
DOI: 10.1038/labinvest.2012.177
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of p38/Mk2 signaling pathway improves the anti-inflammatory effect of WIN55 on mouse experimental colitis

Abstract: P38/Mk2 (mitogen-activated protein kinase (MAPK)-activated protein kinase-2, also known as MAKAP kinase-2) is a member of the mitogen-activated protein kinases (MAPKs) family, and participates in inflammatory responses directly or indirectly. WIN55, 212-2 (WIN55) is a synthetic non-selective agonist of cannabinoid (CB) receptors with remarkable antiinflammatory properties. This study was to explore the roles of WIN55 and p38/Mk2 signaling pathway in dextran sodium sulfate (DSS)-induced mouse colitis and ascert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 51 publications
3
27
0
Order By: Relevance
“…Importantly, the analgesic action induced by taranabant was mediated by CB1 receptors, as it was abolished in CB1 −/− mice. This observation reveals a similar mode of action for both CB1 agonists and inverse agonists and points out the importance of CB1 receptors as a therapeutic aim for future drugs targeting IBS‐C.…”
Section: Discussionsupporting
confidence: 63%
“…Importantly, the analgesic action induced by taranabant was mediated by CB1 receptors, as it was abolished in CB1 −/− mice. This observation reveals a similar mode of action for both CB1 agonists and inverse agonists and points out the importance of CB1 receptors as a therapeutic aim for future drugs targeting IBS‐C.…”
Section: Discussionsupporting
confidence: 63%
“…no. 160110; MP Biomedicals, Solon, OH, USA) for 7 days continuously, as described by Li et al (20). At 7 days after the induction of colitis, stool consistency and the presence of occult blood was examined and documented daily.…”
Section: Methodsmentioning
confidence: 99%
“…The MS was the sum of the three scores, ranging between 0 (healthy) and 12 (maximal). Scoring was conducted as reported previously by Li et al (20) and Kimball et al (21). …”
Section: Methodsmentioning
confidence: 99%
“…Using a panel of synthetic cannabinoids, phytocannabinoids, and eCBs, we found that the synthetic cannabinoid WIN55,212-2 and the eCB NADA have the ability to dampen the activation of primary human lung microvascular ECs (HMVEC-lung) by a variety of inflammatory agonists, including bacterial lipopeptides (TLR2 agonist), lipopolysaccharide (LPS) (TLR4 agonist), and TNF␣. Although the anti-inflammatory properties of WIN55,212-2 have previously been described, only a few reports have described the physiological functions of NADA, including its role in inflammation (16,(25)(26)(27)(28)(29)(30)(31)(32).…”
mentioning
confidence: 99%